COMPARATIVE ANALYSIS OF THE EFFECTIVENESS OF PARENTERAL DRUGS IN THE TREATMENT OF IRON DEFICIENCY ANEMIA IN PREGNANT WOMEN - Juraeva G.T; Najmutdinova D.K; Kobiljonova M (Scholar Express Journals, 2023)
To compare the effectiveness, tolerability and safety of intravenous iron carboxymaltose (ICM) and intravenous iron sucrose for the treatment of moderate iron deficiency anemia in pregnant women
Keywords: moderate; women; effectiveness; iron